EXPLORING LEARNER AUTONOMY IN THE CLASSROOM: AN INVESTIGATION AT THREE SELECTED JUNIOR HIGH SCHOOLS IN JAMBI: Learner Autonomy - Darwina, Darwina; Royani, Hilda; Adawiyah, Rabiatul (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2024)
This research investigated learner autonomy based on English teachers’ perceptions at three selected junior high schools in Jambi. Its aims were to describe how the teachers perceive learner autonomy and to what extent they promote learner autonomy in the classroom. This research used quantitative approach. The data were gathered through questionnaires involving 4 English teachers of SMPN 17 Jambi, 2 English teachers of SMPN 1 Muaro Jambi, and 4 English teachers of SMP IT AL AZHAR. Participants were asked to answer the questions on the questionnaires which consist of 34 items in total. The type of the questions was close-ended questions. After doing the research the data were analyzed by calculating teachers’ responses to find means score and frequency after that interpreting the results of the questionnaires. The results of this study showed that the teachers perceived learner autonomy is quite high with the overall mean score was 3.88. Learner autonomy were highly and very highly promoted in the classroom through the teachers’ role as facilitator, counsellor, resource, and manager.